Pengaruh Faktor Intensitas Cahaya terhadap Jumlah dan Ukuran Stomata Daun Tumbuhan Monokotil di Arboretum Sempaja (Penunjang Materi Jaringan Tumbuhan) - Annisa, Annisa; Herliani, Herliani; Kurniawati, Zenia Lutfi; Serena, Nelda Anasthasia (Biocaster : Jurnal Kajian Biologi, 2025)
The effect of light on stomata has been extensively studied, but studies that specifically observed the effect of light intensity on the size and number of stomata in monocot plants at the Sempaja Arboretum, Samarinda, are still very limited, including monocot plants, and have the potential to be a contextual learning resource for biology education in schools. The purpose of this study is to determine the effect of light intensity on the number and size of stomata in monocot plants in the Sempaja Arboretum. This research was carried out from February to May. This study used a Non-Factorial Group Random Design, with 3 different light intensities (morning, noon, and evening). Based on the results of statistical tests (ANOVA and Duncan's follow-up tests), not all species show statistically significant differences in size and number between times (morning, noon, evening). Some species such as Sri Rejeki (Aglonema sp) and Turmeric (Curcuma longa) show statistically insignificant changes. In other species such as Virginia Flower (Commelina virginica), Palm (Arenga pinnata), and Golden Ivory Betel (Epipremnum aureum), the difference in stomata size between times is more pronounced and significant.